A recommended management plan for coronavirus disease 2019–positive geriatric patients based in South African old age homes - Christina Eleftheriades (South African Family Practice)
The coronavirus disease 2019 (COVID-19) pandemic has had a profound impact on elderly patients, and thus, adequate treatment plans are essential. This qualitative report provides recommendations for the supportive care and treatment of residents in long-term care facilities (LTCF) with COVID-19. A treatment protocol was developed in response to an outbreak of COVID-19 in an LTCF based in Johannesburg and was implemented over a 3-month period.